Pengaruh Oral Hygiene terhadap Dekubitus Mukosa Oral pada Pasien Terpasang Nasogastric Tube - Nabila Fitriana Khairunnisa; Wahyu Rima Agustin; Dian Nur Wulanningrum (Universitas Muhammadiyah Klaten, 2024)
Oral mucosal pressure ulcers is a pressure sore found in the mucous membrane area with a history of using medical devices. The use of NGT is not only to be considered in the administration of nutrition, but also needs to be considered in the oral area. Oral hygiene is defined as the act of cleaning and refreshing the mouth, teeth, and gums. The objective of oral hygiene is to maintain the health of the lips, tongue, and oral mucosa, prevent infection, and moisturise the oral membrane and lips. This research employs quantitative methods and a quasi-experimental design. In this research, the data sampling technique is purposive sampling. The sample used was 42 respondents with inclusion criteria installed nasogastric tube (NGT). Characteristics of respondents aged <60 years were 26 respondents (61.9%) of a total of 42 respondents, while respondents aged >60 years were 16 respondents (38.1%) of a total of 42 respondents. The respondents were characterised according to gender. Of the total number of respondents, 19 were male (45.2%) and 23 were female (54.8%). The results showed that there was an effect of oral hygiene on oral mucosal pressure ulcers in patients with nasogastric tube (NGT) in the ICU room at Dr Moeward Hospital with a p-value of 0.000 (p-value <0.05).